Audio-Lingual Method to Improve Students' English Speaking Skills - Manda, Ibrahim; Hermansyah, Sam (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aimed to determine whether using the Audio-Lingual method improves students' speaking skills at the eighth-grade SMP Negeri 1 Baranti. This research aims to investigate and measure the impact of using the Audio-Lingual method in improving students' English speaking skills. This research used the experimental method. The population of this study was one class of class VIII.1 of SMP Negeri 1 Baranti. In the 2018/2019 academic year, the total population was 23 students. The sample of this study was 23 students. This sample was taken using the cluster random sampling technique. This research applied the Audio-Lingual method in the class. This research applies one type of speaking skills test to determine students' speaking skills. The research results show that using the Audio-Lingual method in teaching speaking can improve the speaking skills of class VIII.1 students at SMP Negeri 1 Baranti. The mean score of the pre-test (54.30) was lower than the mean score of the post-test (57.04), showing that the P-value was lower than the α (0,000 < 0,05) on the significant level of α 0,05. So, the researcher stated that H0 was rejected and H1 was accepted. Based on data analysis, the researcher concluded that the audio-lingual method effectively improved students' speaking skills in class VIII.1 of SMP Negeri 1 Baranti.